2011
DOI: 10.1186/1471-2377-11-55
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia and neuropathic pain - differences and similarities. A comparison of 3057 patients with diabetic painful neuropathy and fibromyalgia

Abstract: BackgroundPatients with diabetic neuropathy (DPN) and fibromyalgia differ substantially in pathogenetic factors and the spatial distribution of the perceived pain. We questioned whether, despite these obvious differences, similar abnormal sensory complaints and pain qualities exist in both entities. We hypothesized that similar sensory symptoms might be associated with similar mechanisms of pain generation. The aims were (1) to compare epidemiological features and co-morbidities and (2) to identify similaritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 28 publications
3
98
1
3
Order By: Relevance
“…Neuropathic pain assessment tools such as the Neuropathic Pain Questionnaire used in this study are increasingly employed as the first step in the diagnostic work-up of persons with chronic pain. Classification of patients into neuropathic and non neuropathic pain syndromes based on verbal descriptors alone, however, is not sufficient for diagnosis in individual patients, since chronic disorders such as painful neuropathy and fibromyalgia may in fact share very similar sensory phenomena (35). …”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain assessment tools such as the Neuropathic Pain Questionnaire used in this study are increasingly employed as the first step in the diagnostic work-up of persons with chronic pain. Classification of patients into neuropathic and non neuropathic pain syndromes based on verbal descriptors alone, however, is not sufficient for diagnosis in individual patients, since chronic disorders such as painful neuropathy and fibromyalgia may in fact share very similar sensory phenomena (35). …”
Section: Discussionmentioning
confidence: 99%
“…74 The most common type of provoked pain by far is dynamic mechanical allodynia, which corresponds clinically to allodynia evoked by gentle brush, and has a prevalence of 18-54% in patients with neuropathic pain. 34,95 Typical examples of dynamic mechanical allodynia include patients with thoracic postherpetic neuralgia who report pain due to contact between skin and shirt; and patients with peripheral neuro pathy who experience pain owing to contact between feet and bed sheets.…”
Section: Anatomical Denervationmentioning
confidence: 99%
“…Neuropathic sensory symptoms, however, did not distinguish TNP from FM. Although in the majority of FM patients no nerve lesion can be detected,37 numerous studies have demonstrated similarities between neuropathic pain patients and FM patients with regard to the experience of sensory symptoms 3. Vierck37 suggested that changes in the milieu of muscles and other deep somatic structures in FM might lead to a similar state of hyperactivity in nociceptive neurons as is observed after nerve damage.…”
Section: Discussionmentioning
confidence: 99%